Multiplex detection and identification of Phytophthora spp. using target‐specific primer extension and Luminex xTAG technology. (16th December 2015) - Kostov, K.; Verstappen, E. C. P.; Bergervoet, J. H. W.; de Weerdt, M.; Schoen, C. D.; Slavov, S.; Bonants, P. J. M.
Abstract : There are more than 100 species that belong to the fungus‐like genus Phytophthora, many of which can cause severe damage to plants in both natural and agricultural ecosystems. The availability of techniques for detection and identification are crucial for monitoring and control of these pathogens. In recent years, new methods using molecular approaches have been developed. However, the majority of them are designed to detect single Phytophthora species. Techniques that are able to target multiple species in one sample would offer advantages, especially for the assessment of Phytophthora diversity in the environment. This paper describes a multiplex assay for simultaneous detection and identification of 26 members of Phytophthora down to species level and another 22 to clade or subclade level through target‐specific primer extension (TSPE) and the Luminex xTAG array detection system. The assay starts with PCR amplification of two genomic regions, ITS and coxI, followed by a multiplex TSPE reaction with clade‐, subclade‐ and species‐specific probes. As a result, biotin‐dCTP labelled products are generated and subsequently detected through hybridization with a set of anti‐TAG coupled, colour‐coded paramagnetic beads. The specificity of the method has been tested using DNA extracts from over 400 isolates representing 110 Phytophthora species and subspecies. The sensitivity and robustness have been determined by the use of DNA mixtures, dilution series and environmental samples. Thus the developed technique allows simultaneous identification of multiple Phytophthora species, particularly useful for the detection of these pathogens in environmental samples such as soil, water and plant tissue.